MOBILE COMMERCE: A REVIEW (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
As the power of wireless increases, it provides various opportunities for improving services to customers. In today’s era, mobile commerce or M-Commerce has entered almost all the aspects of Business organizations like finance, retails, services, telecommunications and information technology services. This paper discusses the concept of Mobile Commerce. It looks at how the technology of Mobile Commerce has facilitated new business trends. After this there is detailed description of applications of M-Commerce, its advantages & disadvantages. In last finally it throws light on the challenges that are faced by M-Commerce.